2009 International Conference on Applied Superconductivity and Electromagnetic Devices 2009
DOI: 10.1109/asemd.2009.5306705
|View full text |Cite
|
Sign up to set email alerts
|

Design and electromagnetic analysis of a HTS linear synchronous motor

Abstract: Abstract-High temperature superconducting (HTS) linear synchronous motor (LSM) integrated with HTS magnetic levitation system, can realize self-levitation and self-guidance without any sliding friction, which will have important applications in many fields such as electromagnetic aircraft launch system, maglev transportation. This paper presents the design and electromagnetic analysis of a HTS LSM, which is levitated by a magnetic levitation system consisting of HTS bulkspermanent magnet (PM) guideways. Numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In order to achieve the decoupling of the coupled equations, the mathematical model of HTSLSM is established under d-q axis coordinate system as follows. 4 Current equation…”
Section: A Closed Loop Control System For the Htslsmmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve the decoupling of the coupled equations, the mathematical model of HTSLSM is established under d-q axis coordinate system as follows. 4 Current equation…”
Section: A Closed Loop Control System For the Htslsmmentioning
confidence: 99%
“…The high temperature superconducting (HTS) linear motors developed so far can be mainly classified by the principle and structure as follows: 1) HTS linear reluctance motor (LRM) with ordinary copper windings on the primary (stator) and zero-field-cooled (ZFC) HTS bulk poles on the secondary (mover) [1,2]; 2) HTS linear synchronous motor (HTSLSM) with ordinary copper windings on the primary and HTS bulk or coil magnets on the secondary [3][4][5][6][7][8][9][10]; 3) HTSLSM and linear induction motor (LIM) with HTS windings on the primary [11,12]. These HTS linear motors can be further divided into single-sided, double-sided, and cylindrical types according to their structures.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the application potential of the HTS maglev, the authors of this paper have developed a prototype vehicle as illustrated schematically in Fig. 1 [5][6][7]. The interaction between the HTS bulks on the movable body and the PM guideways (PMGs) on the ground generates a strong levitation force with passive and self-stabilizing features.…”
Section: Since Hellmanmentioning
confidence: 99%
“…The secondary of the linear motor is placed on the bottom of the vehicle, which can be a PM array for a linear synchronous motor [8] or a copper/aluminum sheet for a linear induction motor [9]. The PMs in the secondary can be replaced by an array of YBCO HTS bulk magnets [10]. With the advance of HTS techniques, it has been reported that HTS bulks can trap a magnetic field well above 2.3 T at 77 K [11].…”
Section: Introductionmentioning
confidence: 99%
“…This paper carries out further analysis of the presented HTS bulk magnet linear synchronous motor (LSM) for driving a HTS maglev vehicle model [10]. The numerical model of HTS bulk magnet is firstly investigated.…”
Section: Introductionmentioning
confidence: 99%